Blood Lead and Reading Readiness - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2013)
Investigators at the University of Maryland School of Nursing, Johns Hopkins School of Public Health, and Department of Health, Providence, Rhode Island, evaluated the relationship between reading readiness test scores for children attending public kindergarten in Providence, RI, and state health department records of blood lead levels (BLLs).